Identification and stability of acylated anthocyanins in purplefleshed sweetpotato p40 - Xu, Jianteng (Kansas State University, 2013)
We previously selected a purple-fleshed sweetpotato p40 clone that has been shown to protect against colorectal cancer in a murine model. This study is to identify anthocyanins by using HPLC/MS-MS and assess the stability during various coking conditions. P40 possesses a high content of anthocyanins up to 13 mg/g dry matter. Total 12 acylated anthocyanins with caffeic, ferulic, and p-hydrobenzoic acid have been identified on either cyanidin or peonidin bases. The top three major anthocyanins are cyanidin 3-caffeoyl-p-hydroxybenzoyl sophoroside-5-glucoside, peonidin 3-caffeoyl sophoroside-5-glucoside, and cyanidin 3-(6'' -caffeoyl-6''-feruloylsophoroside)-5-glucoside, which account for an half of the total anthocyanin contents. Seven non-, mono-, or di-acylated cyanidin species and five mono- or di-acylated peonidin species contribute for 69% and 31% of total anthocyanins, respectively. Over 80% of total anthocyanins measured by acid hydrolysis were cyanidin derivatives. Therefore, as a cyanidin-predominated variety, p40 is unique when compared with other reported purple-fleshed sweetpotatoes that usually contain more peonidin than cyanidin. While baking does not impact overall contents of anthocyanins, steaming, high pressure cooking, microwaving, and frying significantly reduce 20% of total anthocyanin contents. Mono-acylated anthocyanins show a higher resistance against heat than di- and non-acylated. Among of which, cyaniding 3-p-hydroxybenzoylsophoroside-5-glucoside exhibits the best thermal stability. Better understanding of dietary anthocyanins and their stabilities may lead to the development of a functional anthocyanin-enriched sweetpotato product for health benefits.
Keywords: Anthocyanins; HPLC; Thermal stability; Purple sweetpotato; Agriculture, General (0473); Analytical Chemistry (0486)